2019
DOI: 10.1136/bmjopen-2018-028671
|View full text |Cite
|
Sign up to set email alerts
|

The surgical burden of disease and perioperative mortality in patients admitted to hospitals in Victoria, Australia: a population-level observational study

Abstract: ObjectivesComprehensive reporting of surgical disease burden and outcomes are vital components of resilient health systems but remain under-reported. The primary objective was to identify the Victorian surgical burden of disease necessitating treatment in a hospital or day centre, including a thorough epidemiology of surgical procedures and their respective perioperative mortality rates (POMR).DesignRetrospective population-level observational study.SettingThe study was conducted in Victoria, Australia. Access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…34 Academic surgery and research capability in the Pacific and PNG require further development as this will strengthen local leadership and provide evidence on which to base NSOAPs and other capacity building initiatives. Nonetheless, Global Surgical Research from Australia, NZ, Timor, PNG and the Pacific published papers on POMR, 20,[29][30][31][32][33] Bellwether access, 36 the global burden of surgical disease [37][38][39] and the graduation and retention of surgical, obstetric and anaesthesia specialists. 7,40 Lessons learned from the introduction of emergency medicine specialists and their training in PNG, 41,42 informed a successful and rapid implementation in Myanmar.…”
Section: Surgical Metrics and Pomrmentioning
confidence: 99%
“…34 Academic surgery and research capability in the Pacific and PNG require further development as this will strengthen local leadership and provide evidence on which to base NSOAPs and other capacity building initiatives. Nonetheless, Global Surgical Research from Australia, NZ, Timor, PNG and the Pacific published papers on POMR, 20,[29][30][31][32][33] Bellwether access, 36 the global burden of surgical disease [37][38][39] and the graduation and retention of surgical, obstetric and anaesthesia specialists. 7,40 Lessons learned from the introduction of emergency medicine specialists and their training in PNG, 41,42 informed a successful and rapid implementation in Myanmar.…”
Section: Surgical Metrics and Pomrmentioning
confidence: 99%
“…Originating in 1979, the VAED is a comprehensive data set of the causes, effects and nature of the illnesses reported by the health services in Victoria maintained by the Department of Health and Human Services (DHHS) . The VAED collects a minimum set of data for each admitted patient episode to any hospital in Victoria (both public and private).…”
Section: Introductionmentioning
confidence: 99%
“…It also records the procedures the patient underwent during the admission. Reporting of all admissions to VAED is government requirement and is therefore considered to be highly accurate and free of missing data …”
Section: Introductionmentioning
confidence: 99%
“…4 Studies from Sweden, USA, Australia and New Zealand have found surgical procedures are performed for 25% to 35% of all hospital admissions. [5][6][7][8] One challenge facing the Pacific Island nations, Papua New Guinea and Timor Leste during the period of implementing the Sustainable Development Goals is to provide access to surgery and anaesthesia care. Such access would reduce the burden of disease that is amenable to surgical treatment, hence would result in improved health and well-being for the Pacific Island populations.…”
Section: Introductionmentioning
confidence: 99%